Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{168}{10}-x=18.65-\frac{1488}{100}\)
\(\frac{84}{5}-x=\frac{1865}{100}-\frac{1488}{100}\)
\(\frac{84}{5}-x=\frac{377}{100}\)
\(x=\frac{84}{5}-\frac{377}{100}\)
\(x=\frac{1680}{100}-\frac{377}{100}\)
\(x=\frac{1303}{100}\)
\(x=13.03\)
a, 2,5 x 18,65 x 4
= (2,5 x 4 ) x 18,65
= 10 x 18,65
=186,5
k mk nhé
a) 2,5 x 18,65 x 4
= (2,5 x 4) x18,65
= 10 x 18,65
= 186,50
b) 37,15 : 2,5 - 27,15 : 2,5
= (37,15 + 27,15) : 2,5
= 10 :2,5
= 4
đây nha bn
ht
ta co :
x*2*3*4=168
x*2*3=168:4
x*2=42:3
x=14:2
x=7
vay :7*2*3*4=168
cho mih 1 dung nhe
( x + 5 ) + ( x + 10 ) + . . . + ( x + 100 ) = 1110
=> x × 20 + ( 5 + 10 + . . . + 100 ) = 1110
=> x × 20 + 1050 = 1110
=> x × 20 = 60
=> x = 60 : 20
=> x = 3
Số số hạng của dãy là:(100-5):5+1=20
(x+x+...+x)+(5+10+15+...+100)=1110
x × 20+(100+5)×20:2=1110
x×20+1050=1110
x×20=1110-1050
x×20=60
x=60:20
x=3
a. 168x168-168x68
= 168x(168-68)
= 168x100
= 16800
b. 201,5x17-2015x16-201,5
= 201,5x17-201,5x160-201,5
= 201,5x(17-16-1)
= 201,5x0
= 0
c. 1,5 + 1,5x2+1,5x7-10
= 1,5x1+1,5x2+1,5x7-10
= 1,5x(1+2+7)-10
= 1,5x10-10
= 10x(1,5-1)
= 10x0,5
= 5
d. 1,25x2,5x64
= 1,25x64x2,5
=80x2,5
= 200
a)168*168-168*68=168*(168-68)=168*100=16 800
b)201,5*17-2015*16-201,5=201,5*17-201,5*160-201,5=201,5*(17-160-1)=201,5*(-144)=-29016
c)1,5+1,5*2+1,5*7-10=1,5*(1+2+7)-10=1,5*10-10=(1,5-1)*10=0,5*10=5
d)1,25*2,5*64=1,25*2,5*8*8=(1,25*8)*(2,5*8)=10*20=200
\(x:\frac{1}{2}+x:\frac{1}{4}+x:\frac{1}{100}=\frac{106}{10}\)
\(Xx2+Xx4+Xx100=\frac{106}{10}\)
\(Xx\left(2+4+100\right)=\frac{106}{10}\)
\(Xx106=\frac{106}{10}\)
\(X=\frac{106}{10}:106\)
\(\Rightarrow X=\frac{1}{10}\)
Ta có :
\(x:\frac{1}{2}+x:\frac{1}{4}+x:\frac{1}{100}=\frac{106}{10}\)
\(\Leftrightarrow\)\(2x+4x+100x=\frac{106}{10}\)
\(\Leftrightarrow\)\(x\left(2+4+100\right)=\frac{106}{10}\)
\(\Leftrightarrow\)\(106x=\frac{106}{10}\)
\(\Leftrightarrow\)\(x=\frac{106}{10}:106\)
\(\Leftrightarrow\)\(x=\frac{106}{10}.\frac{1}{106}\)
\(\Leftrightarrow\)\(x=\frac{1}{10}\)
Vậy \(x=\frac{1}{10}\)
2 ( x + 10 ) + 20 = 100
2 ( x + 10 ) = 100 - 20
2 ( x + 10 ) = 80
( x + 10 ) = 80 : 2
x + 10 = 40
x = 40 - 10
x = 30
Vậy x = 30